Effect of ultrasound on the cleaning of root canal system: a literature review - Jardel da Silva, Leandro (2019)
The cleaning of root canal system is one of the principal factors in determining the success of endodontic treatment. Thus, complementary irrigation to the instrumentation plays a fundamental role in the removal of bacteria, dentin remains and therapeutic materials. In addition, the irrigation method is primordial to ensure the cleaning efficiency of the root canal system; it can be performed manually by syringe and needle, but also by using specific devices for this purpose, such as ultrasound. The objective of this study was to perform a review of the literature on the effect of ultrasound on the cleaning of root canal system. An electronic search was performed in the PubMed, LILACS and Cochrane Library databases, with the terms "passive ultrasonic irrigation", "root canal" and "endodontic irrigation". Articles were selected based on the inclusion and exclusion criteria. It was concluded that passive ultrasonic irrigation is effective as the elimination of bacteria, calcium hydroxide, dentin debris and smear layer, using sodium hypochlorite (NaOCl) as an irrigating solution, thus allowing an optimization in the cleaning of root canal system.